First Schistosomal Cholecystitis Complicated by Cholangitis and Liver Abscess: Case Report and Review of Literature - Ali Toffaha; Samir Al Hyassat; Walid Elmoghazy; Hatem Khalaf; Ahmed Elaffandi (Case Reports in Surgery)
Schistosomiasis is one of the most prevalent parasitic infections in the developing world. When it affects the gastrointestinal system specifically the liver, it causes periportal fibrosis followed by cirrhosis. Cholecystitis however is a rare presentation, and associated liver abscess has certainly never been reported to date. We report a case of acute cholecystitis complicated by cholangitis and liver abscess in a 46-year-old man. After complex course of treatment, he had laparoscopic cholecystectomy, and the histology report confirmed schistosomiasis. Gallbladder schistosomiasis is an uncommon disease that is associated with dense fibrotic changes that strongly mimics xanthogranulomatous cholecystitis. Liver abscess may occur during the disease evolution especially in patient originating from endemic backgrounds. We present the case and a comprehensive literature review.